The Positive Effect of Four-Week Combined Aerobic-Resistance Training on Body Composition and Adipokine Levels in Obese Females - Purwo Sri Rejeki; Adi Pranoto; Ilham Rahmanto; Nabilah Izzatunnisa; Ghana Firsta Yosika; Yetti Hernaningsih; Citrawati Dyah Kencono Wungu; Shariff Halim (MDPI AG, 2023)
Obesity is a metabolic disease that is caused by a lack of physical activity and is associated with an increased risk of chronic inflammation. A total of 40 obese adolescent females with an average age of 21.93 ± 1.35 years and average body mass index (BMI) of 30.81 ± 3.54 kg/m2 were enrolled in this study, randomized, and divided into four groups, i.e., control (CTL; n = 10), moderate intensity aerobic training (MAT; n = 10), moderate intensity resistance training (MRT; n = 10), and moderate intensity combined aerobic-resistance training (MCT; n = 10). The enzyme-linked immunosorbent assay (ELISA) kits method was used to analyze the adiponectin and leptin levels between pre-intervention and post-intervention. Statistical analysis was conducted using a paired sample t-test, while correlation analysis between variables used the Pearson product-moment correlation test. Research data showed that MAT, MRT, and MCT significantly increased adiponectin levels and decreased leptin levels compared to the CTL (p ≤ 0.05). The results of the correlation analysis of delta (∆) data showed that an increase in adiponectin levels was significantly negatively correlated with a decrease in body weight (BW) (r = −0.671, p ≤ 0.001), BMI (r = −0.665, p ≤ 0.001), and fat mass (FM) (r = −0.694, p ≤ 0.001) and positively correlated with an increase in skeletal muscle mass (SMM) (r = 0.693, p ≤ 0.001). Whereas, a decrease in leptin levels was significantly positively correlated with a decrease in BW (r = 0.744, p ≤ 0.001), BMI (r = 0.744, p ≤ 0.001), and FM (r = 0.718, p ≤ 0.001) and negatively correlated with an increase in SMM (r = −0.743, p ≤ 0.001). In summary, it can be concluded that our data show that adiponectin levels increased and leptin levels decreased after the intervention of aerobic, resistance, and combined aerobic-resistance training.